Предмет: Математика,
автор: enot991
sina*sinb/cosa*cosb .
Ответы
Автор ответа:
0
Известно, что y=PI-(a+b), тогда
cos y=-cos(a+b)), siny=sin(a+b).
-(sin a cos b+cos a sin b)cos(a+b)=
sin(a+b)(-cos a cos b+sin a sin b),
-sin(a+b)cos(a+b)=-sin(a+b)cos(a+b).
cos y=-cos(a+b)), siny=sin(a+b).
-(sin a cos b+cos a sin b)cos(a+b)=
sin(a+b)(-cos a cos b+sin a sin b),
-sin(a+b)cos(a+b)=-sin(a+b)cos(a+b).
Похожие вопросы
Предмет: Математика,
автор: robert7574
Предмет: Алгебра,
автор: Аноним
Предмет: Английский язык,
автор: calayka
Предмет: Алгебра,
автор: 18Andrey18